Local Group cosmology - Martínez-Delgado, David (Cambridge University Press, 2013)
"One of the most fascinating unresolved problems of modern astrophysics is how the galaxies we observe today were formed. The Lambda-Cold Dark Matter paradigm predicts that large spiral galaxies such as the Milky Way formed through accretion and tidal disruption of satellite galaxies, a notion previously postulated on empirical grounds from the character of stellar populations found in our Galaxy. The Local Group galaxies are the best laboratory in which to investigate these galaxy formation processes because they can be studied with sufficiently high resolution to exhume fossils of galactic evolution embedded in the spatial distribution, kinematics, and chemical abundances of their oldest stars"--Provided by publisher
Includes bibliographical references
Lectures presented at the XX Canary Islands Winter School of Astrophysics, held in Tenerife, Spain, November 17-18, 2008
Keywords: Local Group (Astronomy) -- Congresses; Konferenzschrift; Lokale Gruppe